Polycyclic aromatic hydrocarbons in the coastal environment of Peninsular Malaysia and their bioavailability to Paphia undulata Born - Keshavarzifard, Mehrzad (2015)
Polycyclic aromatic hydrocarbons (PAHs) with two or more benzene rings are one of the most important classes of pollutants. PAHs contamination is a great global concern due to their negative effects on human health and environmental consequences, such as toxic, mutagenic, carcinogenic, teratogenic and hepatotoxic effects. Therefore, their sources, pathways, distributions and fate in the environment and ecosystems are important to be monitored. Samples were collected from selected rivers and estuaries in Peninsular Malaysia from January to May 2013. Samples were homogenized, freezedried, extracted, cleanup, fractionated and analyzed using gas chromatography mass spectrometry. In this study, the distributions and sources of PAHs in the surface sediments from the Kedah, Merbok, Prai, Perak, Klang and Malacca Rivers and Estuaries and Paphia undulata (short-neck clam) from the Kedah, Merbok, Prai, Perak, Klang and Malacca Estuaries were monitored, and also the bioavailability of PAHs to Paphia undulata from sediments were evaluated. The concentrations of total PAHs in sediments varied from 195.2 to 7938 ng g -1 dry weight (dw) and in Paphia undulata varied from 179.97 to 1657.5 ng g -1 dw. PAHs in sediments can be classified as moderate in the Kedah and Perak, moderate to high in the Merbok and Malacca and high to very high in the Prai and Klang Rivers and Estuaries. PAHs in the soft tissues of Paphia undulata can be classified as moderate. The comparison of PAHs with Sediment Quality Guidelines (SQGs) indicates that occasionally adverse biological effects may occur at the Stations 1, 2 and 3 of the Klang River, Station 1 of the Prai River and at Station 2 of the Merbok River, and severe adverse biological effects may occur from low molecular weight (LMW) PAHs at the Stations 1 of the Prai River. The diagnostic ratios of individual PAHs in sediments and Paphia undulata indicated both petrogenic and pyrogenic origin PAHs with significantly dominance of pyrogenic source. The calculated biota-sediment accumulation factor (BSAF) values of total PAH ranged from 0.27 to 0.84. The results clearly showed that Paphia undulata from the Merbok, Prai, Perak, Klang and Malacca Estuaries had larger BSAF values for LMW PAHs, while those from the Kedah Estuary showed higher BSAF values for high molecular weight (HMW) from the sediment. The results of this study indicated that acenaphthene (Ace), fluorene (Fl), phenanthrene (Phe) and naphthalene (Nap) had the highest bioavailability, while benzo[k]fluoranthene (BkF), anthracene (Ant), dibenzo [a, h] anthracene (DBA) and benzo [b] fluoranthene (BbF) had the lowest bioavailability. Based on the findings of this study Paphia undulata can be introduced as a good biomonitor of contamination and bioavailability of hydrocarbon pollution in estuary ecosystems of Peninsular Malaysia. The results also indicated that under environmental conditions, the sedimentary load of hydrocarbons appears to be one of the factors controlling their bioavailability. The concentrations of total n-alkanes (nC10-nC36) ranged from 1365 to 15850 and from 1875 to 34270 μg g-1 dw, in sediment and short-neck clam samples, respectively. The results of this study indicated that the n-alkanes in the sediment and Paphia undulata samples originated from diverse sources. Biogenic sources such as algal remains, aquatic organisms, and terrestrial plants are all considered to be a source of n-alkanes. The C29/C30 hopanes ratios were similar with those of Middle East Crude Oil (MECO), suggesting MECO as a major source of petroleum hydrocarbons for Malaysian sedimentary.